Effects of ferrochromium slag with neat and polymer modified binders in hot bituminous mix - Yılmaz, Mehmet; Kök, Baha Vural (My University, 2009)
In this study the properties of hot bituminous mix containing ferrochromium slag with neat and styrene-butadiene-styrene modified binders have been investigated. The ferrochromium slag is used as coarse aggregate and total aggregate. Three different binders, B 50/70, B 160/220 and B 160/220+3% SBS, are used in mixtures. The physical and mechanical properties of polymer modified binders and binder-aggregate mixes are evaluated in terms of their fundamental engineering properties such as dynamic shear rheometer (DSR), rotational viscometer (RV) for binders, Marshall stability, indirect tensile stiffness modulus, tensile strength and moisture susceptibility for mixtures. It has been concluded through the laboratory tests that using ferrochromium slag as coarse aggregate provided satisfactory results. The usage of ferrochromium slag as total aggregate does not exhibit good performance in terms of stability and stiffness modulus. However, the mixtures prepared entirely with ferrochromium slag showed good resistance to moisture damage. It is found that in spite of the similarity between high temperature performance grades of B 50/70 and B 160/220+3% SBS, the mechanical properties of the mixtures prepared with these binders do not show the same performance.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Hot bituminous mix; Ferrochromium slag; Stability; Stiffness modulus; Moisture susceptibility